2023
DOI: 10.1186/s12883-023-03176-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on neuropsychiatric and sleep disorders, and quality of life in individuals with neurodegenerative and demyelinating diseases: a systematic review and meta-analysis of observational studies

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has affected the mental health, sleep and quality of life, especially in individuals with chronic disease. Therefore, the purpose of this systematic review and meta-analysis was to investigate the impact of the COVID-19 pandemic on neuropsychiatric disorders (depression, anxiety, stress), sleep disorders (sleep quality, insomnia) and quality of life in individuals with Parkinson’s disease (PD), Multiple Sclerosis (MS) and Alzheimer's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Some studies have shown how occupational disruptions affected specified domains of health. For example, occupational disruption has been reported to produce serious negative effects on physical health ( Kiuchi, Kishi & Araki, 2020 ; Marconcin et al, 2022 ), mental health ( Chien, 2022 ; De Oliveira et al, 2023 ; Marconcin et al, 2022 ), psychological resilience ( Karimi Khordeh et al, 2022 ; Killgore et al, 2020 ), social relationships ( Long et al, 2022 ; Ottoni, Winters & Sims-Gould, 2022 ; Philpot et al, 2021 ), and quality of life ( De Oliveira Almeida et al, 2023 ; De Oliveira et al, 2023 ; Kan et al, 2023 ; Kandula & Wake, 2021 ). However, such studies have been limited to one or a few domains.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown how occupational disruptions affected specified domains of health. For example, occupational disruption has been reported to produce serious negative effects on physical health ( Kiuchi, Kishi & Araki, 2020 ; Marconcin et al, 2022 ), mental health ( Chien, 2022 ; De Oliveira et al, 2023 ; Marconcin et al, 2022 ), psychological resilience ( Karimi Khordeh et al, 2022 ; Killgore et al, 2020 ), social relationships ( Long et al, 2022 ; Ottoni, Winters & Sims-Gould, 2022 ; Philpot et al, 2021 ), and quality of life ( De Oliveira Almeida et al, 2023 ; De Oliveira et al, 2023 ; Kan et al, 2023 ; Kandula & Wake, 2021 ). However, such studies have been limited to one or a few domains.…”
Section: Introductionmentioning
confidence: 99%